Communities Leading Change: Using Implementation Science to Improve Physical Activity and Nutrition Among Racially Minoritized Communities in Kansas City. - Lightner, Joseph S.; Gardiner, Kelsey; Grimes, Amanda; Shook, Robin P.; Hampl, Sarah; Prochnow, Tyler; Collie-Akers, Vicki (Health Promotion Practice, 2026)
Kansas City, Missouri (United States) is the fifth most economically and racially segregated city in the United States. Black and Latino individuals in Kansas City die up to 18 years earlier than non-Hispanic White individuals. The historical divestment has led to communities on Kansas City's east side having deleterious environments for physical activity and lack of access to healthy food. As a result, these residents, primarily Black and Latino community members, are disproportionately burdened by chronic diseases such as obesity, diabetes, and heart disease. The purpose of this project is to reduce health disparities in chronic disease by increasing physical activity, improving nutrition, and increasing participation in family healthy weight programs for Black and Latino families in Kansas City. This implementation and research protocol describes the Centers for Disease Control and Prevention (CDC)-funded collaborative agreement "Communities Leading Change" to improve long-term health among Black and Latino families in Kansas City. In the short term, we will improve policies, plans, and community design that increases access to physical activity, improve access to fruit and vegetables, and increase support for an evidence-based family healthy weight program. This initiative may inform future practice, policy, and research by providing an example of a long-term funded project that is community-driven and uses partnerships to create policy, systems, and environmental change.